PENGARUH MARKET SHARE, KECAKAPAN MANAJERIAL, DAN MANAJER YANG MEMPUNYAI HUBUNGAN POLITIK TERHADAP TINGKAT KESEHATAN PERUSAHAAN BADAN USAHA MILIK NEGARA (BUMN) DI INDONESIA - Elok Fitriya; Zaki Baridwan; Endang Mardiat (STIE Mandala Jember, 2016)
This study aims to determine the effect of market share, managerial skills,and managers who have political ties to the soundness of state-owned companies inIndonesia. Data were collected in the form of financial statements of companieslisted on the SOE Ministry in 2011 until 2013. The research sample, a company thathas the financial data are complete and already in the audit. Hypothesis testingusing Multiple Linear Regression with SPSS version 19. The results prove thatmanagers who have political relations are the factors that determine the level ofhealth of state-owned companies in Indonesia. Meanwhile, the value of market shareand managerial skills is a factor that does not determine the health condition ofstate-owned companies in Indonesia.